2018
DOI: 10.1590/1678-4162-9292
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do tratamento antirrábico humano pós-exposição, associado a acidentes com cães

Abstract: RESUMO O estudo da profilaxia da raiva humana contribui para orientação quanto ao uso de vacinas e soros antirrábicos, servindo de base para a definição de estratégias de prevenção, controle e avaliação da doença. Objetivou-se avaliar o atendimento antirrábico humano pós-exposição e possíveis incompatibilidades com o protocolo do Ministério da Saúde, em agressões por cães, no município de Belo Horizonte. Analisaram-se as fichas de atendimento antirrábico do SINAN para comparação dos tratamentos prescritos com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 13 publications
5
8
0
1
Order By: Relevance
“…Table 1 showed a 71.1% (1,843) agreement between the treatments instituted by the health service and those recommended by the Ministry of Health (MS), represented by the sum of the treatments present in the main diagonal of the table. This result corroborates Cabral et al (2018), who found a 67.2% agreement between the treatment performed by the health service and that recommended by the Ministry of Health. Fernandes ( 2013) also observed a 70% agreement.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Table 1 showed a 71.1% (1,843) agreement between the treatments instituted by the health service and those recommended by the Ministry of Health (MS), represented by the sum of the treatments present in the main diagonal of the table. This result corroborates Cabral et al (2018), who found a 67.2% agreement between the treatment performed by the health service and that recommended by the Ministry of Health. Fernandes ( 2013) also observed a 70% agreement.…”
Section: Resultssupporting
confidence: 90%
“…Among the treatments adopted by the health service in accordance with the Ministry of Health, the treatment combining the animals' observation and the use of the human rabies vaccine stood out, representing 48.3% (1,251/2589). It corroborates Cabral et al (2018), who found 46.5% of the consultations involving animal observation associated with the use of the human rabies vaccine in accordance with the Ministry of Health's protocol.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Data regarding dog bites are mainly obtained from studies from hospitals and health services offered by the Unified Health System (SUS). The epidemiological analysis of these data, as well as the identification of geographic areas associated with cases of canine aggression, could help to prevent many fatal attacks by using appropriate and effective prophylactic measures (Rosado et al 2007;Cabral et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Cabral et al (2018) apesar de ser uma doença passível de prevenção, a raiva continua sendo uma importante causa de mortalidade humana em muitos países, representando um grande desafio para as autoridades sanitárias.…”
Section: Introducãounclassified